Self-Disproportionation of Enantiomers of Chiral, Non-Racemic Fluoroorganic Compounds: Role of Fluorine as Enabling Element - Sorochinsky, Alexander E.; Aceña, José Luis; Soloshonok, Vadim A. (Synthesis, 2013)
This review discusses all available literature on the self-disproportionation of enantiomers (SDE) of fluorine-containing compounds, resulting in a separation of racemic form from the excess enantiomer. Included are examples of the SDE via distillation, sublimation and achiral chromatography. The role of fluorine on the magnitude and preparative efficiency of the SDE, as a new, nonconventional method for optical purifications, is emphasized and critically discussed.1 Introduction2 General Aspects of Fluorine Influence on the Self-Disproportionation of Enantiomers3 Self-Disproportionation of Enantiomers via Distillation4 Self-Disproportionation of Enantiomers via Sublimation5 Self-Disproportionation of Enantiomers via Achiral Chromatography6 Conclusions
Keywords: fluorine; fluorine compounds; optical purification; chiral recognition; chromatography; physicochemical phase transitions; amino acids; amines; hydroxy acids